- IoT-Based Attendance System Using Data Storage on Google Spreadsheet and Smart Door Lock In Computer Labs: - - Pratama, Irfan; AYUNINGSIH, EKATRI (Cattleya Darmaya Fortuna, 2023)
Before carrying out learning and teaching activities in the computer lab, the thing that needs to be considered is the presence of students. Absence is something that must be done by lecturers and students to find out the number of attendance. The presence of students is used as a parameter for evaluating lecturers and the academic section to determine whether students are allowed to take the midterm and final exams. The output of this study is an IoT-Based attendance system using data storage on Google Spreadsheet and Smart Door Locks in the computer lab. In this study using a 3 x 4 keypad, arduino uno, and jumper cables.The tools used to retrieve attendance data are nodeMCU, Card Reader, Jumper Cable, LCD and Google Spreadsheet as data storage.